DAKWAHTAIMENT “EXISTENCE OF DAKWAH IN THE TELEVISION INDUSTRY IN INDONESIA: THE FIGHT BETWEEN SYIAR AND MARKET SEGMENTATION - Mhd. Syahirul A. Rambe; Haris Muda Panasean Lubis; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
ABSTRACTThe advantages of industrial technology have achieved unprecedented efficiency, so that they are able to produce information, communication and transportation tools so cheaply and in such a short time. Too much freedom. One of the products of this transformation is the proliferation of these da'wahtainment programs which essentially combine "Guidance and Spectacle" for the people, as their operational basis for profit through the commodification of religion alone. The use of technology in fulfilling the spiritual needs of the Indonesian people continues to develop its existence as a consequence of the modernization of the times. Da'wahtainment as a model of da'wah on television is one of the colors of the development of da'wah media through the use of technology. As one of the strategic da'wah methods, da'wahtainment is very helpful in the process of spiritual development for some of our society. A dilemma of the da'wahtainment program is when the packaging of the da'wah method with entertainment often invites public perception. Keywords: Existence of Da'wah, TV Industry, Broadcasting and Market Interests